ANALISIS GEOPOLITIK TERHADAP PERANG PROKSI ARAB SAUDI-IRAN SEBAGAI BENTUK PERGOLAKAN KAWASAN TIMUR TENGAH - Azzahra, Saradiva (Journal of Integrative International Relations, 2020)
This paper seeks to explain how the situation in the Middle East conflict has not yet reached its final phase. Iran and Saudi Arabia became key actors in the various upheavals that occurred in the Middle East region. Both of them compete with each other to achieve their national interests. This condition is considered as the source of a number of conflicts in the Middle East involving allied countries. Nonetheless, basically the political competition between Saudi Arabia and Iran continues to increase. Allied countries that are on the side of Iran and Saudi Arabia are considered to have certain goals and interests in this situation. This paper also analyzes the occurrence of this proxy war from the perspective of geopolitical studies. This paper also focuses on the strategies used by each country in maintaining interests in the region which are also the cause of upheaval in the Middle East region. The author believes that both Iran and Saudi Arabia are making mutual efforts in terms of balance of power to achieve regional hegemony.